The Level of Intolerance among Students of the College of Applied and Educational Sciences in Al-Nadrah. (مجلة جامعة سرت للعلوم الانسانية, 2025)
The research aimed to determine the level of fanaticism  among students  College of Applied and Educational Sciences in Al Nadrah , and   identify the nature of differences in intolerance among college students according to variables (gender, academic specialization, academic level, and marital status). The sample included (120) male and female students who were selected using a simple random sampling  method, from the third and fourth levels, and from various academic specializations. The researcher constructed a scale of intolerance among university students. After verifying the validity and reliability of the scale in more than one way, it was applied to the research sample. The results showed that the level of fanaticism  among the research sample was high, as the achieved arithmetic mean for the sample reached (112.16) points, compared to (102) for the hypothetical mean of the scale. There were statistically significant differences between the two averages at the level of (0.05) in favor of the achieved mean. The highest level of fanaticism  among the sample members was in the area of fanaticism . The results also indicated that there were no statistically significant differences in fanaticism according to the gender variable in all areas of the scale, except for the total score of the sample, where statistically significant differences were found in favor of males. In the educational level variable, the results indicated that there were statistically significant differences between third and fourth year students in the area of sexual fanaticism and the total score in favor of third year students. No statistically significant differences were found in the rest of the areas (intellectual, political, and tribal). In the educational specialization variable, statistically significant differences were found at the (0.5) level in the area of political fanaticism, in favor of those with scientific specialization. No differences were found in the rest of the scale areas. In the marital status variable (single - married), the results indicated that there were no statistically significant differences at the level of areas and the total score in the level of fanaticism. Recommendations and proposals were made in accordance with the research results
Keywords: Intolerance; College of Applied and Educational Sciences